Grizzlies and gazelles: Duty factor is an effective measure for categorizing running style in English Premier League soccer players - Hanley, Brian; Tucker, Catherine B.; Gallagher, Liam; Parelkar, Parag; Thomas, Liam; Crespo, Rubén; Price, Rob J. (Frontiers in Sports and Active Living, 2022)
English Premier League soccer players run at multiple speeds throughout a game. The aim of this study was to assess how well duty factor, a dimensionless ratio based on temporal variables, described running styles in professional soccer players. Twenty-five players ran on an instrumented treadmill at 12, 16 and 20 km/h. Spatiotemporal and ground reaction force data were recorded for 30 s at each speed; video data (500 Hz) were collected to determine footstrike patterns. In addition to correlation analysis amongst the 25 players, two groups (both N = 9) of high and low duty factors were compared. Duty factor was negatively correlated with peak vertical force, center of mass (CM) vertical displacement and leg stiffness (kleg) at all speeds (r ≥ –0.51, p ≤ 0.009). The low duty factor group had shorter contact times, longer flight times, higher peak vertical forces, greater CM vertical displacement and higher kleg (p < 0.01). Eight of the high DF group players were rearfoot strikers at all speeds, compared with three in the low group. Duty factor is an effective measure for categorizing soccer players as being on a continuum from terrestrial (high duty factor) to aerial (low duty factor) running styles, which we metaphorically refer to as “grizzlies” and “gazelles”, respectively. Because duty factor distinguishes running style, there are implications for the training regimens of grizzlies and gazelles in soccer, and exercises to improve performance should be developed based on the biomechanical advantages of each spontaneous running style.